Production of human mutant biologically active hepatocyte growth factor in Chinese hamster ovary cells. Issue 5 (28th May 2017) - Xu, Dongsheng; Wan, Aini; Peng, Lin; Chen, Yun; He, Yang; Yang, Jianfeng; Jin, Jian
ABSTRACT: Hepatocyte growth factor (HGF) is a potent multifunctional cytokine that affects proliferation, migration, and morphogenesis of various cells. HGF is secreted as an inactive single-chain precursor protein and activated by the cleavage of serine proteases to form heterodimers. In our current study, the cleavage site of HGF was blocked by replaced Arg 494 of Glu (R494E) that resulted in the single-chain HGF (R494E) unable to be cleaved by serine proteases. We established Chinese hamster ovary (CHO) cells overexpressing HGF (R494E), the expression of HGF (R494E) achieved 12 mg/L and was similar to a previously reported study. The recombinant protein was then purified from culture medium using a two-step chromatographic procedure that resulted in about a 40% recovery rate. The purified HGF (R494E) was obtained as a single-chain active protein. It concluded that HGF (R494E) exhibited a biologically active protein and the overexpressing CHO cell line supplied sufficient material for future studies. The R494E replacement of the cleavage site would be beneficial to the utility of other similar therapeutic proteins.